Pelayanan Kesehatan Berbasis Aplikasi Android Electronic-Jantung di Rumah Sakit Umum Daerah Kramat Jati - Rizky, Alfina; Zulmasyhur, Zulmasyhur (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
This study uses a descriptive qualitative analytical methodology to investigate healthcare services facilitated by the E-Jantung Android application at Kramat Jati Regional General Hospital. The study findings indicate positive advancements in terms of responsiveness and accountability. Responsiveness is evident in users favourable responses to the application and the assistance provided by hospital staff to those in need. Additionally, the hospital has implemented support mechanisms such as a complaint box, demonstrating a commitment to accountability principles that involve community participation in service development. Nevertheless, this research underscores the significance of application refinement, with particular attention to user feedback, particularly from the elderly population. Furthermore, addressing technical issues through updates is of utmost urgency to ensure the optimal functioning of technology-based healthcare services. Finally, a more extensive awareness campaign is imperative, especially for the elderly demographic, who may be less familiar with the E-Heart application.